Seismo-Hydrogeodynamic Effects Caused by the Earthquake on April 3, 2023, Mw=6.6: As Observed in Wells on the Kamchatka Peninsula - Kopylova G.N.; Boldina S.V. (MDPI AG, 2024)
An earthquake with magnitude of Mw = 6.5–6.6 occurred on April 3, 2023 near the eastern coast of Kamchatka Peninsula (northwest of Pacific seismic belt) at a depth of H = 95 km, causing shaking with intensity of 6 points on the 12-point MSK-64 scale in the Petropavlovsk-Kamchatsky geodynamic test site, where long-term observations of groundwater pressure in wells are carried out. In wells YuZ-5, E-1, 1303, M-1, located at epicentral distances de = 67–77 km (hypocentral distances dh = 116–122 km), various changes in groundwater pressure/level were recorded: (i) oscillations due to passage of seismic waves, (ii) coseismic jumps of water pressure caused by a change in the static stress state of water-bearing rocks during the formation of rupture in the earthquake source (coseismic effects); (iii) post-seismic effects. In the well E-1, within 93 days before earthquake, a hydrogeodynamic precursor was recording as a lowering in water level/pressure at increased rate. Using this precursor, identified in real time, a forecast conclusion on the strong earthquake possibility was submitted in advance to the Kamchatka branch of the Russian Expert Council for Earthquake Forecasting. The earthquake that occurred was consistent with the forecast in magnitude, time, and location. Seismo-hydrogeodynamic effects in water pressure/level changes recorded in wells YuZ-5 and E-1 corresponded to the previously created typifications of such phenomena for these wells. The issues of creation and verification of seismo-hydrogeodynamic effect typifications for individual observation wells for predicting strong earthquakes and studying the influence of seismicity on groundwater are discussing.
Keywords: 37.31.19 Сейсмология; 38.61.03 Методы гидрогеологических исследований; 38.61.15 Динамика и режим подземных вод